Abnormalities of the testes and epididymis in bucks and rams slaughtered at Debre Zeit abattoir, Ethiopia - Regassa, F.; Terefe, F.; Bekana, M. (Springer, 2003)
A study was conducted at Debre Zeit export abattoir on 404 bucks belonging to four breeds and 167 rams of two breeds. The animals were selected from the slaughter flock using stratified sampling based on breed. Ante-mortem and post-mortem examinations were carried out after each animal was carefully identified. Various genital abnormalities were observed, among which testicular atrophy and epididymitis were the predominant genital problems in both bucks and rams. The prevalence of cryptorchidism was higher (p<0.05) in bucks than in rams, while epididymitis (p<0.05), sperm granuloma (p<0.01) and epididymal cysts (p<0.05) were more frequent in rams. In bucks, none of these abnormalities was significantly associated with age (p>0.05). However, testicular atrophy (p<0.01), epididymitis (p<0.01) and haemorrhagic lesions (p<0.05) were associated with breed, the prevalence being higher in Woito-Guji and Boran bucks than in the Arsi-Bale and Afar breeds. In rams, age affected (p<0.05) the incidence of testicular atrophy, epididymitis and sperm granulomas. Epididymitis, sperm granuloma and epididymal cysts were more frequent (p<0.01) in Adal rams than in Black Head Somalis.